2021
DOI: 10.3389/fonc.2021.759842
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TRIM54/Axin1/β-Catenin Axis Prohibits Proliferation and Metastasis in Hepatocellular Carcinoma

Abstract: Accumulating evidence demonstrates that dysregulation of ubiquitin-mediated degradation of oncogene or suppressors plays an important role in several diseases. However, the function and molecular mechanisms of ubiquitin ligases underlying hepatocellular carcinoma (HCC) remain elusive. In the current study, we show that overexpression of TRIM54 was associated with HCC progression. TRIM54 overexpression facilitates proliferation and lung metastasis; however, inhibition of TRIM54 significantly suppressed HCC prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Furthermore, SOCS2 enhances the radiotherapy sensitivity of patients with HCC through mediated SLC7A11 ubiquitination ( Chen et al, 2022 ). Furthermore, TRIM54 was identified as an oncogene in HCC ( Zhu et al, 2021 ). Köster et al have demonstrated that a high level of PSMD9 is strongly associated with clinical relapse after radiotherapy in patients with cervical cancer ( Köster et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SOCS2 enhances the radiotherapy sensitivity of patients with HCC through mediated SLC7A11 ubiquitination ( Chen et al, 2022 ). Furthermore, TRIM54 was identified as an oncogene in HCC ( Zhu et al, 2021 ). Köster et al have demonstrated that a high level of PSMD9 is strongly associated with clinical relapse after radiotherapy in patients with cervical cancer ( Köster et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In GBC cells, TRIM37 has been found to interact with Wnt/β‑catenin signaling pathway, although the mechanisms behind this remain unknown [ 11 , 12 , [18] , [19] , [20] , [21] ]. It has been shown in previous studies that the E3 ubiquitin ligases, such as RNF146, TRIM11, TRIM32, TRIM54, TRIM65 and UBE3C promote various cancers by triggering Wnt/β-catenin signaling via degradation of Axin1 [22] , [23] , [24] , [25] , [26] , [27] . Axin1 and GSK-3β are two key regulators of the Wnt/β-Catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoprecipitation was performed according to our published studies [20]. Lysates from 3 × 10 6 cells transfected with the indicated constructs were incubated with myc-, or Flag-conjugated agarose beads (Sigma-Aldrich, Germany) overnight at 4°C.…”
Section: Immunoprecipitationmentioning
confidence: 99%
“…Western blotting was performed according to our published studies [20]. The primary antibodies were:antiag (Sigma-Aldrich, F3165), anti-RNF149 (HPA011424, Sigma-Aldrich), anti-myc (ab32, Abcam), anti-HA (Abcam, ab9110), and anti-PHLPP2 (ab227673, Abcam).…”
Section: Akt Activity Assaymentioning
confidence: 99%